2019
DOI: 10.5465/ambpp.2019.190
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Human Development

Abstract: We examine the human development consequences of FDI. We propose an inverted-U shaped relationship between inward FDI and human development in a host country. We also suggest this effect weakens with strong host-country institutions. Our analysis, based on a dataset of 139 countries over 15 years, supports our hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The review of empirical literature that focused on the determinants of human development revealed that the effects of factors such as income (Ranis et al, 2000, 2000; Suri et al, 2011), globalization (Nguea et al, 2020; Welander et al, 2015), tourism (Riveira, 2017), ICT (Acheampong et al, 2021; Asongu & Le Roux 2017), economic complexity (Ferraz et al, 2018; Hartmann, 2014; Vu, 2020), foreign direct investment (Orbes et al, 2019; Reiter & Steensma, 2010), and natural resource rents (Noumba et al, 2022; Sinha & Sengupta, 2019) on human development have mainly been investigated. We focused on separate factors that were sparse in earlier studies, for instance, urbanization, demographic dividend and biomass energy consumption, and divided the literature into three sections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The review of empirical literature that focused on the determinants of human development revealed that the effects of factors such as income (Ranis et al, 2000, 2000; Suri et al, 2011), globalization (Nguea et al, 2020; Welander et al, 2015), tourism (Riveira, 2017), ICT (Acheampong et al, 2021; Asongu & Le Roux 2017), economic complexity (Ferraz et al, 2018; Hartmann, 2014; Vu, 2020), foreign direct investment (Orbes et al, 2019; Reiter & Steensma, 2010), and natural resource rents (Noumba et al, 2022; Sinha & Sengupta, 2019) on human development have mainly been investigated. We focused on separate factors that were sparse in earlier studies, for instance, urbanization, demographic dividend and biomass energy consumption, and divided the literature into three sections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aside from their relative stability, FDI inflows present numerous benefits to recipient or host economies. Several empirical studies have confirmed the benefits of FDI to host economies (Lee et al ., 2020; Lihn et al ., 2019; Orbes et al ., 2019). These benefits include improved managerial techniques, economic growth/development (Dellis et al ., 2017), employment generation (Kurtishi-Kastrati, 2013), higher tax revenues (Udeh and Odo, 2017), technological spillovers (Loukil, 2016; Navas, 2019) amongst others.…”
Section: Introductionmentioning
confidence: 99%